PENGARUH UKURAN BUTIRAN AGREGAT TERHADAP KUAT TEKAN DAN MODULUS ELASTISITAS BETON KINERJA TINGGI GRADE 80 - Purwati, Agus; As'ad, Sholihin; Sunarmasto, Sunarmasto (Program Studi Teknik Sipil FT UNS, 2014)
The use of reactive materials with finer grains, like mikrosilica (silica fume) and superplasticizer enables to produce a more dense concrete with lowwater-cement ratio. Extra dense concrete improves the concrete compressive strength. One way to increase the concrete compressive strength withextra dense concrete manufacture is applying micro-sized particle filler. In addition, aggregate gradation plays an important role in determining thequality of the high performance concrete is grade 80. If the aggregates are finer and their grain are vary, the pore volume of concrete will be less.This is due the tiny grains that fill the pores between the larger grains. Less pore in concrete that leads to form more compact concrete. This studyaims to acces the compressive strength and modulus of elasticity of high performance concrete by varying the size of the aggregates. The study used anexperimental method with a total of 18 samples, there were 3 variations of each sample. Specimens used by cylinder in diameter 7.62 cm and15.24 cm in height. The compressive strength and modulus of elasticity of concrete were tested at the 28 days of concrete age. Compressive strengthof concrete with a larger grain size has a value lower compressive strength than concrete with a small grain size. Concrete made of aggregate size 19mm has the lowest compressive strength recorded 42.66 MPa and its modulus of elasticity was 16366.887 MPa and concrete made of aggregatesize 0.85 mm has the higest compressive strength recorded 84.7 MPa and its modulus of elasticity was 24870.674 MPa. Good aggregategradation will be able to result in maximum density and minimum porosity. This generates higher compressive strength in concrete.